PENGARUH DIABETIK SELF MANAGEMENT EDUCATION (DSME) TERHADAP RESIKO TERJADINYA ULCUS DIABETIK - Azissah, Danur (JURNAL MEDIA KESEHATAN, 2017)
The sufferers’ incapable in carried out DM type 2 is one of the most caused it. Diabetic Self-Management Education (DSME) is the method which can stimulate of patients’ knowledge; skill andability in doing the self-care for prevent the ulcers’ diabetic. The aim of this research is to find out theinfluence of DSME toward the risk of consistence of ulcers’ diabetic for path treatment’s patients ofmellitus diabetes (MD) type 2 at Pukesmas Jalan Gedang of Bengkulu’s working area in year 2016.The method of this research is quasi-experimental with pre-test and post-test approach. SimpleRandom Sampling is used to divided the 66 respondent in 2 groups i.e. intervention and controlgroups. The result showed that the influence of DSME toward risk of consistence of ulcers’ diabeticbefore DSME (p=0,329) whereas, after DSME (p=0,020); with improvement of knowledge beforeDSME (p=0,135),after DSME (p=0,027); and leg treatment behavior before DSME (p=0,135)whereas, after DSME (p=0,041); as well as self-confidence before DSME (p=0,454) whereas, afterDSME (p=0,002) by value (≤α=0,05). It can conclude that there is a significant influence of DSMEtoward risk of consistence of ulcers’ diabetic for path treatment’s patients of mellitus diabetes (MD)type 2 at Pukesmas Jalan Gedang Bengkulu’s Working Area in year 2016. This research can be inputinformation for the health’s staff. In order, it can give the knowledge and the health promotion aboutthe influence of DSME toward the risk of consistence of ulcers’ diabetic.